Strukturwandlungen und Entwicklungstendenzen der orientalischen Stadt.: Versuch eines Überblicks - Wirth, Eugen (ERDKUNDE, 1968)
Most of near-eastern cities today appear as a very interesting mixture of ancient, traditionally oriental elements, of modern elements of purely western pattern and of elements of an acculturation taking place simultaneously with a re-orientalizing process. Owing to these converging influences the larger cities show quite a number of highly characteristic features: 1. The traditional trading center, the bazaar and the neighbouring khans, have lost their importance in part, although it seems surprising that they succeeded yet in retaining a large part of their functions to this day. However, in several ways they have been subject to deep functional changes. 2. In addition to the bazaar modern commercial quarters of western style have developed in preferred districts of younger parts of the town. Normally these do not compete with the bazaar, but supplement it in many respects besides being frequented by entirely different buyers. 3. Outside the bazaar the medieval part of the city has lost much of its social prestige as a residential quarter. Obviously this district today more than ever represents the seat of the traditional crafts. 4. The more recent residential quarters outside the medieval city belong to the most westernized parts of the near eastern town. Recently here have taken place various social transformations. 5. The long-distance road traffic and the motor vehicle prescribe to a very high degree the layout of many districts or even the entire fundamental structure of today's near eastern city.